Conflict Between Bir Shumshere and C.E.R. Girdlestone - Mainali, Kashi Kanta (Tribhuvan University Journal, 2011)
Available with fulltext. Key words: History of Prime Minister; Bir Sumshere; Nepal Tribhuvan University Journal Vol XXIII, No. 1, 2001 Page: 111-118 Uploaded date: 21 April, 2011